Analysis of the Financing and Return on a Geothermal Investment – Case Study - Jenei, Tünde (International Journal of Engineering and Management Sciences, 2018)
Implementing a geothermal energy investment involves a significant amount of capital investment for a local government which cannot be realized only from its own sources therefore, it is necessary to involve external financial resources. In this article, I look at what resources the local government can get involved in implementing the investment planned by the local government. I also analyse the different combinations of these sources and when using different resources, how does the internal return on investment and its net present value change.